Uint-Packing: Multiply Your DNN Accelerator Performance via Unsigned Integer DSP Packing - Zhang, Jingwei; Zhang, Meng; Cao, Xinye; Li, Guoqing (2023 60th ACM/IEEE Design Automation Conference (DAC), 2023)
DSP blocks are undoubtedly efficient solutions for implementing multiply-accumulate (MAC) operations on FPGA. Since DSP resources are scarce in FPGA, the advanced solution is to pack parallel multiplication operations into a single DSP. However, available methods are based on signed-type multiplication, leading to both loss of accuracy and increased area. To solve these issues simultaneously, we propose an unsigned integer DSP packing generalization model called uint-packing. Guided by this generalization model, we design the novel computational structure of the DNN accelerator. Our system design is state-of-the-art, with 2.8× throughput and 4× energy efficiency compared to the third-place DAC-SDC'22 design.